Capital raising, underwriting and the certification hypothesis - Booth, James R.; Smith, Richard L. (Journal of Financial Economics, 1986)
This paper develops a theory of the role of the underwriter in certifying that risky issue prices reflect potentially adverse inside information. The theory derives from the literature on the use of reputational capital to guarantee product quality. An underwriting cost/benefit paradigm is employed to generate testable implications related to announcement effects, issue underpricing, the choice of competitive versus negotiated underwriting, and the level of underwriter compensation as a function of firm-specific information. Existing empirical literature is reviewed in the context of the certification hypothesis and several new tests are conducted. All of the findings are supportive of the hypothesis.